2023
DOI: 10.1071/fp23049
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis reveals key metabolites and metabolic pathways in Suaeda salsa under salt and drought stress

Abstract: Suaeda salsa is an important salt- and drought-tolerant plant with important ecological restoration roles. However, little is known about its underlying molecular regulatory mechanisms. Therefore, understanding the response mechanisms of plants to salt and drought stress is of great importance. In this study, metabolomics analysis was performed to evaluate the effects of salt and drought stress on S. salsa. The experiment consisted of three treatments: (1) control (CK); (2) salt stress (Ps); and (3) drought st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Tryptophan and isoleucine indicated that significantly increase with water deficit stress ( Ignjatovic-Micic et al., 2015 ; Kong et al., 2022 ). However, it has also been demonstrated that only drought-tolerant cultivars have higher tryptophan levels ( Bao et al., 2023 ), and tryptophan metabolites can enhance plant stress resistance under adverse conditions ( Hasnain et al., 2023 ). ABC transporter proteins have certain drought-resistant capabilities under drought stress and provide triacylglycerol to glycerol kinase ( Han et al., 2022 ), which then stimulates the synthesis of sucrose ( Sharma and Nayyar, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tryptophan and isoleucine indicated that significantly increase with water deficit stress ( Ignjatovic-Micic et al., 2015 ; Kong et al., 2022 ). However, it has also been demonstrated that only drought-tolerant cultivars have higher tryptophan levels ( Bao et al., 2023 ), and tryptophan metabolites can enhance plant stress resistance under adverse conditions ( Hasnain et al., 2023 ). ABC transporter proteins have certain drought-resistant capabilities under drought stress and provide triacylglycerol to glycerol kinase ( Han et al., 2022 ), which then stimulates the synthesis of sucrose ( Sharma and Nayyar, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests common metabolic strategies to tolerate (anion agnostic) osmotic stress in roots at the root-soil interface and restrict sodium translocation, while leaves might be more susceptible to the (anion dependent) ion toxicity of translocated Cland SO4 2-. The generalised salt response included common accumulation of the phenylpropanoid precursor 2-phenylacetamide in leaves (a salt biomarker in the euhalophyte Suaeda salsa (Bao et al, 2023)), protective molecules in stems such as the anthocyanin ternatin C5 (Kovinich et al, 2015) and a highly antioxidative coumaric acid conjugate of salicin, grandidentatin (Si et al, 2009), as well as potential cell wall structural components in roots, such as the monolignol precursors syringin.…”
Section: Salt Anion Identity Shapes Salix Metabolomic Tolerance Respo...mentioning
confidence: 99%